Políticas públicas de inclusão social e de incentivo à conservação do meio ambiente: propostas para a (re) adaptação do bolsa verde como forma de efetivação da sustentabilidade socioeconômica ambiental - Assis, Luciana Vilar de (2020)
When it comes to public policies related to the environment, it can be emphasized that governments and societies have started to discuss ways and establish alternatives to the implementation of conducts that meet the precepts of sustainable development. Such actions became part of the priorities in meetings involving environmental law around the world and daily life showed that awareness about the potential of environmental damage, as well as its implications on quality of life throughout the planet, are indispensable elements in encouraging human conduct that seeks sustainable solutions to problems involving the environment. In line with this new stance adopted in societies, that of taking sustainable actions, governments have been promoting ideas and programs aimed at public policies in order to minimize the incidence of behaviors considered predatory in the face of the abusive use of environmental resources. It is in this scenario that the Environmental Conservation Support Program - Bolsa Verde, Program of the Federal Government, established in 2011 and extinct in 2018, is included, aimed at families who were in extreme poverty and that added economic, social and environmental aspects, aiming at an improvement in the quality of life, not only of the beneficiary, but of the whole society. The research under this study has as a problem to ascertain whether Bolsa Verde was able to meet the purposes of its institution and, as a consequence of this proposition, presents hypothesis in the sense that the program promotes social inclusion and the sustainable use of natural resources in the territory of the families benefited. Among the objectives of the research is the identification of the effectiveness of the Program and the investigation whether the beneficiary families complied with environmental legislation in addition to developing activities of conservation and sustainable use of natural resources. The correlation between receiving the benefit and improving the quality of life of the beneficiaries is a highlight, but the lack of actions that bring environmental education to a necessary and indispensable level for the construction of a more critical posture on the part of the population involved ends up tarnishing the mediated purposes of the program. At the end of the text are the proposals for alternatives for the redeployment and readaptation of the Bolsa Verde Program, with its possible return to the public policy platforms of the federal government, taking into account, therefore, the precepts that involve the national environmental policy established in the country, as well as foundations of sustainable development and environmental education as indispensable elements of awareness of the population directly involved in this kind of socio-environmental platform.